Construction of DNA probe diagnostic for psychodopygus complexus (Diptera, phelebotominae), a suspected vector of Leishmania (viannia) braziliensis vianna in Pará, State - Souza, Adelson Alcimar Almeida de (1992)
Trabalho apresentado no Congresso da Sociedade Brasileira de Medicina Tropical, 28., 1992, Belém.